Astaxanthin treatment ameliorates ER stress in polycystic ovary syndrome patients: a randomized clinical trial - Masoome Jabarpour; Ashraf Aleyasin; Maryam Shabani Nashtaei; Sara Lotfi; Fardin Amidi (Scientific Reports, 2023)
Abstract Astaxanthin (ASX), as a natural carotenoid compound, exists in various types of seafood and microorganisms. It has several possible beneficial therapeutic effects for patients with polycystic ovary syndrome (PCOS). Patients with PCOS also suffer from endoplasmic reticulum (ER) stress. In the present work, it was hypothesized that ER stress could be improved by ASX in PCOS patients. Granulosa cells (GCs) were obtained from 58 PCOS patients. The patients were classified into ASX treatment (receiving 12 mg/day for 60 days) and placebo groups. The expression levels of ER stress pathway genes and proteins were explored using Western blotting and quantitative polymerase chain reaction. To assess oxidative stress markers, follicular fluid (FF) was gained from all patients. The Student’s t test was used to perform statistical analysis. After the intervention, ASX led to a considerable reduction in the expression levels of 78-kDa glucose-regulated protein (GRP78), CCAAT/enhancer-binding protein homologous protein (CHOP), and X-box-binding protein 1 compared to the placebo group, though the reduction in the messenger RNA (mRNA) expression level of activating transcription factor 6 was not statistically significant. However, ASX significantly increased the ATF4 expression level. GRP78 and CHOP protein levels represented a considerable decrease in the treatment group after the intervention. In addition, a statistically significant increase was found in the FF level of total antioxidant capacity in the treatment group. Based on clinical outcomes, no significant differences were found between the groups in terms of the oocyte number, fertilization rate, and fertility rate, but the ASX group had higher rates of high-quality oocytes, high-quality embryo, and oocyte maturity compared to the placebo group. Our findings demonstrated that ER stress in the GCs of PCOS patients could be modulated by ASX by changing the expression of genes and proteins included in the unfolding protein response. Trial registration This study was retrospectively registered on the Iranian Registry of Clinical Trials website ( www.irct.ir ; IRCT-ID: IRCT20201029049183N, 2020-11-27).